Spectrophotometric Determination of Flutamide in Pharmaceutical Formulation - Devala Rao, Garikapati (Asian Journal of Chemistry, 2016)
Two simple, sensitive and precise spectrophotometric methods (Method A and Method B) are developed for the determination of flutamide (FMD) in pure and dosage forms. These methods are based on the formation of coloured species on treatment of reduced FMD with 1,10-phenanthroline and Fe(III) [Method A] and diazotization followed by coupling with α-naphthylarnine [Method B].